Taming A Surgeon’s Worst Nightmare – A Case Series Emphasizing Early Detection of Complications Following Whipple’s Resection and Their Successful Management - Rahul Kushagra; Ashwin Krishnamoorthy; Mohan Kumar R; Chandramohan K; Madhu Muralee; Mira Wagh (National Journal of Medical Research)
Pancreaticoduodenectomy (Whipple’s resection) is by far one of the most complicated procedures in surgery with tedious dissection, multiple anastomoses and a stormy postoperative course. The post operative management of these cases may be extremely challenging due to the varied nature of complications involved. Here we present a case series of 5 patients with a varied spectrum of postoperative complications. 3 patients had vascular complications, 1 had pancreatic leak and 1 had efferent loop syndrome. The various methods used to deal with such complications are described.